NATURAL TRANSFORM, STUDI KASUS TEMUAN FRAGMEN KERAMIK DI PARIT KELILING KOMPLEKS CANDI PLAOSAN - Stanov Purnawibowo (Berkala Arkeologi Sangkhakala, 2006)
Archaeological records were not exactly describe the past, transformation proccesses can describe processed of making archaeological records. Natural Transform and Natural Secondary Context were find at encircle ditch of Candi Pfaosan Compleks. The position of deposit archaeological records and stratigraphy can give information about the transformation processes and remainds context were found in the archaeological records